Response of Yield, Water Use Efficiency and Economics of Broad Bean to Irrigation and Phosphorous Level in Lower Indo-Gangetic Plains of Eastern India - Patra, S. K.; Pramanik, Sanjit; Ray, R.; Acharjee, P.; Modak, M. K. (International Journal of Bio-resource and Stress Management, 2021)
The field experiment was conducted during the winter seasons of 2009–10, 2010–11 and 2011–12 on a sandy loam soil of lower Indo-Gangetic plains of Eastern India to optimize irrigation schedule and phosphorus level on broad bean. The treatments comprised of three irrigation levels viz. 30, 60 and 90 mm of cumulative pan evaporation (CPE) and four phosphorus levels viz. 0, 30, 60 and 90 kg P2O5 ha-1 were laid out in a split plot design. The results showed that irrigation at CPE 30 mm and phosphorus at 90 kg P2O5 ha-1 registered significantly the highest average seed yield of 4.76 and 5.37 t ha-1, respectively. The interaction effects revealed that irrigation at CPE 30 mm with 90 kg P2O5 ha-1 recorded significantly mean maximum yield (5.69 t ha-1) and gross return (Rs. 45520 ha-1), net return (Rs. 28870 ha-1) and BCR (1.73). In limited water availability, higher seed yield (5.13 t ha-1), maximum WUE (37.18 kg ha-1 mm-1), higher gross return (Rs. 41040 ha-1), net return (Rs. 25590 ha-1) and BCR (1.66) were found with irrigation at CPE 90 mm with 90 kg P2O5 ha-1. Significant linear relationships were detected between yield with applied irrigation water (R2=0.964) and phosphorus (R2=0.989). Thus imposition of irrigation at CPE 90 mm coupled with 90 kg P2O5 ha-1 could be recommended to broad bean growers for deriving higher yield, WUE and income.